Cemili Divanı - Demircioğlu, Tülay Gençtürk (My University, 2002)
This thesis includes not only a transcribed edition of the Divan by Cemilî who is one of the sixteenth century poets, but also an analysis on his poetry. Chapter 1 or introduction section gives a brief historical and political background on the affairs in such regions as Tebriz, Diyarbakır and Herat, those where Cemilî lived before moving to İstanbul. Chapter 2 focuses on the examination of some critical literary biographies called tezkire, and other sources in order to write about his biography, and to search for other works except his Divan. This chapter also examines various aspects of his poetry. Chapter 3 includes an examination of the Divan on the basis of its form, content and style within three sections. In the first section, formal aspects are questioned in terms of versification, meter scheme, rhyme and redif. In the second section, content is analyzed through the structural organization of the Divan within two subsections. First, one of the significant parts where poet talks conventionally about his own poetics, i.e. dibace, is examined. Then essential themes in gazels are analyzed in terms of not only conventional issues in the classical poetry but also Cemilî's way of using them in his Divan providing with textual examples. In the third section, grammatical, orthographic and rethorical aspects are discussed on the basis of his world of images, word plays and repetitions. In one of the subsections titled as Effects, Cemilî and his poems are compared to those in Garaibü's-sıgar and Fevayidü'l-kiber by Nevayî in order to understand Nevayî's effect on Cemilî. Because Cemilî is also affected by Fuzulî, another famous poet affected by Nevayî, similar poems between Cemilî and Fuzulî are tried to find out in this subsection. Chapter 4 discribes textual characteristics of the Divan and explains the methodology followed in the text edition. Chapter 5 provides a Latin transcription of the Divan including 220 pages i.e. varak. In the conclusion part, various findings are evaluated. Index, the last section, provides a dictionary compiled from words in the Divan. It includes words in Chagatay Turkish and their meanings in western Turkish.

Bu çalışmanın 'Giriş' bölümünde Cemilî'nin XV-XVI. yüzyıllarda İstanbul'a gidene kadar yaşadığı yerler Tebriz, Diyarbakır ve Herat'ta bu yüzyıllarda vuku bulan tarihî ve siyasî gelişmelerden kısaca bahsedilmiştir. Daha sonra şairin hayatı ve başka eserlerinin olup olmadığının ortaya çıkarılması için tezkire ve diğer kaynaklardan elde edilen bilgiler değerlendirilerek hayat hikâyesi ve edebî kişiliği ortaya konmaya çalışıldı. Divan'ın 'şekil özellikleri' bölümünde nazım biçimleri, vezin, kafiye, redif ve imlâ ele alınmıştır. Bu bölümün ikinci kısmı muhteva özellikleri bölümünü içerir.Burada önce şairin poetikasını anlattığı 'dibace' bölümü üzerinde durulmuş, ardından gazellerde işlenen temel konular ele alınmıştır. 'Aşk-sevgili-rakip-zahid-rind-şarap-felekten şikâyet' gibi divanda öne çıkan bu konuların önce Klâsik edebiyatta ne şekilde yer aldığı verildikten sonra bunların Cemilî Divanı'ndaki kullanılışları metinden örnek beyitlerle anlatıldı. Son bölümde dil özellikleri, atasözü ve deyimler, söz ve anlam sanatlarının kullanılışı, şairliği (Hayal Dünyası, İkilemeler, Kelime Oyunları, Tekrarlar ve Etkiler). 'Etkiler' bölümünde şairin Nevayî'den ne derece etkilendiğini bir nebze olsun görebilmek amacıyla Cemilî'nin, Nevayî'nin Garaibü's-sıgar ve Fevayidü'l-kiber'deki şiirlerine benzerlikleri tespit edilebildikleri ölçüde örneklendirilmiştir. Ayrıca Fuzulî'den de (Fuzulî'nin de Nevayî'den etkilendiğini biliyoruz) etkilenmiş olan Cemilî'nin Fuzulî'nin şiirlerine benzeyenler yine bu çalışmanın sınırları ölçüsünde örneklendirildi. Dördüncü bölüm olan 'Nüshanın Değerlendirilmesi' bölümünde nüshanın özellikleri verilerek nüsha tavsifi yapıldı ve metin tesbitinde izlenen yol açıklandı. Altıncı bölümde ise 220 varaktan oluşan Cemilî Divanı'nın transkripsiyonlu metni verildi. Bu incelemeden elde edilen bilgiler 'Sonuç' kısmında değerlendirildi. 'İndeksler' bölümünde ise metinde geçen Çağatay ve Batı Türkçesine ait kelimelerin sözlüğü yapıldı. İndeksler bölümünde ise sözlük-indeks ve metnin indeksi yer alır. Sözlük-indekste hem metnin söz varlığını ortaya koymak hem de bundan sonraki çalışmalara biraz da olsa katkı sağlamak amacıyla metinde geçen Çağatayca ve Batı Türkçesine ait sözcükler aldıkları eklerle birlikte gösterildi.
Keywords: Türk Edebiyatı